In utero/lactational and adult exposures to 2, 3, 7, 8-tetrachlorodibenzo-p-dioxin (TCDD) show differential effects on craniofacial development and growth in rats. (4th November 2015) - Sholts, Sabrina B.; Korkalainen, Merja; Simanainen, Ulla; Miettinen, Hanna M.; Håkansson, Helen; Viluksela, Matti
Abstract: In a previous study of female Han/Wistar (H/W) and Long–Evans (L–E) rats, we found that adult exposure to 2, 3, 7, 8-tetrachlorodibenzo- p -dioxin (TCDD) was associated with size decreases in the cranium and especially the face. In this study we compared these crania to those from male and female Sprague-Dawley (S-D) rats with in utero /lactational exposure to TCDD, using morphometric variables of size, shape, and fluctuating asymmetry to quantify the effects of dose on craniofacial development and growth. At the highest levels of exposure, in utero /lactational and adult TCDD exposures both resulted in small but significant reductions in facial size parameters ( i . e ., 3–5%) in only females and minor effects on facial shape in both sexes. The shape effects of in utero /lactational exposure were most significant at the sutural intersections, whereas adult exposure to TCDD corresponded to dose-dependent changes of decreasing facial length and vault breadth. Fluctuating asymmetry in general explained a relatively small amount of shape variation compared with other effects, and only increased significantly in female L–E rats with high levels of adult exposure to TCDD. These results indicate that TCDD-related changes in cranial development and growth in rats can vary with the timing and duration of exposure, and with sex. Further investigations of other dioxin-like compounds and animal species will broaden our understanding of how chemicals exposure can influence the development and growth of the mammalian skeleton.